2018
DOI: 10.1002/jnr.24248
|View full text |Cite
|
Sign up to set email alerts
|

Tremor severity in Parkinson's disease and cortical changes of areas controlling movement sequencing: A preliminary study

Abstract: There remains much to learn about the changes in cortical anatomy that are associated with tremor severity in Parkinson's disease (PD). For this reason, we used a combination of structural neuroimaging to measure cortical thickness and neurophysiological studies to analyze whether PD tremor was associated with cortex integrity. Magnetic resonance imaging and neurophysiological assessment were performed in 13 nondemented PD patients (9 women, 69.2%) with a clearly tremor-dominant phenotype. Cortical reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Several studies have also demonstrated the presence of tremor-related activity in cerebral cortical structures (Ibanez et al, 2014;Raethjen, Govindan, Kopper, Muthuraman, & Deuschl, 2007). In line with this, changes in the integrity of frontal and parietal areas involved in movement sequencing might be associated with tremorgenic activity in ET (Benito-León et al, 2019), similar to that suggested for Parkinson's disease (Benito-León et al, 2018). Notwithstanding, very little is known about the underlying causes and alterations in brain networks, mainly those involved in nonmotor manifestations in ET, and, hence, further study is needed.…”
Section: Introductionmentioning
confidence: 55%
“…Several studies have also demonstrated the presence of tremor-related activity in cerebral cortical structures (Ibanez et al, 2014;Raethjen, Govindan, Kopper, Muthuraman, & Deuschl, 2007). In line with this, changes in the integrity of frontal and parietal areas involved in movement sequencing might be associated with tremorgenic activity in ET (Benito-León et al, 2019), similar to that suggested for Parkinson's disease (Benito-León et al, 2018). Notwithstanding, very little is known about the underlying causes and alterations in brain networks, mainly those involved in nonmotor manifestations in ET, and, hence, further study is needed.…”
Section: Introductionmentioning
confidence: 55%
“…Several electrophysiological and imaging studies have strongly confirmed the major role of the cerebello-thalamo-cortical network in the pathogenesis of ET (Schnitzler et al, 2009;Lenka et al, 2017;Nicoletti et al, 2020). Furthermore, a large number of studies confirmed the important role of a neural circuit involving frontal and parietal areas in movement sequencing (Bortoletto and Cunnington, 2010;Benito-León et al, 2018). The frontoparietal network was thought to be associated with ET (Oliveira et al, 2012;Benito-León et al, 2015;Cao et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies reported that the parietal operculum was correlated with tremor amplitude-related activity in PD and had distinct activation characteristics among PD patients with differed tremor responsiveness (Dirkx et al, 2019). Moreover, the thickness of inferior parietal gyrus which overlapped with parietal operculum in a portion was found to be associated with tremor severity in PD (Benito-Leon et al, 2018), and the secondary somatosensory cortex was discovered as an important node in the tremor related oscillatory network through magnetometer (Pollok et al, 2009). Secondly, this significant relationship strengthened that the alteration of cholinergic connectivity was quite different between two PD groups with distinct tremor responsiveness and indicated that the distinct cholinergic reactivity of parietal operculum during levodopa administration may be an underlying mechanism for the differed DA responsiveness of tremor in PD.…”
Section: Cholinergic Reactivity Of Parietal Operculum Is Distinct Among Pd Patients With Differed Da Responsiveness Of Tremormentioning
confidence: 85%
“…It is reported that the severity of parkinsonian tremor (including resting tremor and action tremor), unlike bradykinesia, rigidity or postural abnormalities, was not related to the degree of dopaminergic denervation (Benito-Leon et al, 2018). Furthermore, the anticholinergics were found to be preferentially efficient for tremor compared with other parkinsonian symptoms (Cantello et al, 1986;Koller, 1986).…”
Section: Cholinergic System Is Important For the Distinct Tremor Responsiveness In Pdmentioning
confidence: 99%